Tissue Factor Expression on Mesothelial Cells is Induced during in vitro Culture – Manipulation of Culture Conditions Creates Perspectives for Mesothelial Cells as a Source for Cell Seeding Procedures on Vascular Grafts - Verhagen, Hence J M; Heijnen-Snyder, Glenda J; Vink, Tom; Pronk, Apollo; Vroonhoven, Theo J M V van; Eikelboom, Bert C; Sixma, Jan J; Groot, Philip G de (Thrombosis and Haemostasis, 1995)
Lining the luminal surface of prosthetic small diameter bypasses with endothelial cells (EC) will lower its thrombogenicity. Unfortunately, human EC are only scarcely available. Mesotheliai cells (MC) have antithrombotic properties in vivo and can be harvested in large numbers, from the omentum. Recent work demonstrated that the expression of tissue factor (TF) is induced in MC after isolation and culture. Different culture conditions were studied to suppress TF-expression.MC grown in pooled human serum (HS) are procoagulant (717 ± 119 pM factor Xa/min.105 cells). Replacing HS for fetal calf serum, precoating the surface with extracellular matrix and the addition of the xanthine-oxidase inhibitor allopurinol, inhibited TF expression by 90% (p <0.001). Allopurinol clearly reduced TF-mRNA levels.TF expression on cultured MC is an in-vitro effect due to culture conditions and the formation of oxygen free radicals. By reducing TF expression by 90%, we have established conditions in which MC are a good alternative for EC for seeding on synthetic grafts.